Heterogeneous Association of Chinese Adolescents’ Engaged Living With Problematic Internet Use: A Mixture Regression Analysis - Zhang, Jieting; Jiao, Can; Yu, Chengfu; Qiao, Tianqi; Li, Zhirong (Frontiers in Psychology, 2021)
The present study explored heterogeneity in the association between engaged living (i.e., social integration and absorption) and problematic Internet use (PIU). This study included 641 adolescents in four junior-senior high schools of Guangzhou, China. Besides the standard linear regression analysis, mixture regression analysis was conducted to detect a certain subgroups of adolescents, based on their divergent association between engaged living and PIU. Sex, age and psychological need were further compared among the latent subgroups. The results showed that mixture regression model could explain for more variance of PIU than tradition linear regression model, and identified three subgroups based on their class-specific regression of PIU to engaged living. For Class 1, lower social integration and higher absorption were associated with increased PIU; for Class 2, only high social integration was linked with the increase of PIU; for Class 3 with low PIU, no relations between engaged living and PIU were found. Additionally, being male or lower satisfied psychological need increased the link between engaged living and PIU. The results indicated a heterogeneous relationship between engaged living and PIU among adolescents, and prevention program should be tailored specifically to each latent subgroup classified by mixture regression model.